Experimental and numerical investigations of square concrete-filled double steel tubular stub columns. Issue 11 (August 2021) - Ci, Junchang; Ahmed, Mizan; Jia, Hong; Chen, Shicai; Zhou, Daxing; Hou, Liqun
In this paper, the structural behavior of concrete-filled double steel tubular (CFDST) stub columns composed of square hollow sections is investigated experimentally and numerically. The experimental program comprises compression tests on short columns loaded concentrically. The test parameters mainly focused on the influences of the width-to-thickness ratios of steel tubes and concrete strength on the axial behavior of CFDST stub columns. Finite element (FE) models are also developed to investigate the influences of a wide range of structural parameters on their axial performance. It is observed that square CFDST columns have improved strength and ductility compared to their CFST and DCFST counterparts. Finally, a calculation formula is proposed to predict their ultimate compressive strengths under the axial compression load.